Factors Associated with the Incidence of Missed Nursing Care (MNC) - Abdul Rahman La Ede; Johan Budhiana; Ida Ida (GLOBAL HEALTH SCIENCE GROUP, 2025)
Nurses are one of the main elements in health services in hospitals. The main task of nurses is to provide safe nursing care to patients including activities to help patients reduce weakness, prevent disease, and assist in the recovery process without being missed or delayed (Missed Nursing Care). Many factors influence missed nursing care. The purpose of this study was to determine the factors associated with the incidence of missed nursing care at Bhayangkara Setukpa Hospital, Lemdiklat Polri. This type of research is correlational with a cross-sectional approach. Population and sample were all health workers in Bhayangkara Setukpa Lemdiklat Polri Hospital, Sukabumi City, 71 people using total sampling. Data collection using questionnaires. The instrument used in this study was standardised instrument The Missed Nursing Care (MISSCARE) Survey. Data were analyzed using univariate analysis with frequency distribution and bivariate analysis with Chi-Square correlation. Age (p = < 0.001, OR = 7.875), gender (p = 0.018, OR = 0.29), education (p = 0.007, OR = 0.254), length of service (p = < 0.001, OR = 6.214) and marital status (p = 0.002, OR = 0.159) were associated with missed nursing care. There is a relationship between age, gender, education, length of service, and marital status with the incidence of missed nursing care.